Strong, Fast, Fit, Lean, and Safe: A Positional Comparison of Physical and Physiological Qualities Within the 2020 Australian Women's Rugby League Team. (December 2021) - Minahan, Clare; Newans, Tim; Quinn, Karlee; Parsonage, Jo; Buxton, Simon; Bellinger, Phillip
Abstract : Abstract: Minahan, C, Newans, T, Quinn, K, Parsonage, J, Buxton, S, and Bellinger, P. Strong, Fast, Fit, Lean, and Safe: A positional comparison of physical and physiological qualities within the 2020 Australian Women's Rugby League team. J Strength Cond Res 35(12S): S11–S19, 2021—The purpose of the present study was to report the physical and physiological characteristics of elite women Rugby League (RL) players. Thirty-nine women (25.6 ± 4.3 years, 171.3 ± 7.7 cm, 83.5 ± 13.9 kg) from the 2020 Australian women's RL squad were recruited for this study. Players were categorized as adjustables ( n = 7), backs ( n = 15), or forwards ( n = 17) for analysis. Each player was assessed for anthropometry, body composition (dual-energy X-ray absorptiometry), speed (5, 10 and 20 m sprint times), lower-body power (countermovement jump), upper-body power (medicine ball throw and explosive push up force), estimated one repetition maximum (e1RM) bench press, squat and bench pull, isometric mid-thigh pull strength, eccentric knee flexor strength, isometric hip abduction and adduction, and intermittent endurance performance (30–15 intermittent fitness test; 30–15 IFT). Linear mixed models were performed to compare positional groups. Forwards were significantly heavier and had greater fat mass, fat-free mass, and body fat percentage compared with backs and adjustables ( P < 0.01). Backs were faster over 20 m compared with forwards ( P = 0.025), whereas forwards had a lower 30–15 IFT peak velocity and estimated V[Combining Dot Above]O2 peak compared with backs and adjustables. Nonetheless, when including body mass in the model, there were no differences between groups in 30–15 IFT peak velocity. There were no significant differences in other variables. These results provide contemporary benchmark physical, physiological, and anthropometric data for elite women RL players, which can inform recruitment, selection, training, and testing.